ANALISIS SEMANGAT KERJA PADA DINAS PARIWISATA KOTA BIMA - Anggitasari Anggitasari; M Badar (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to determine and analyze how morale at the Bima City Tourism Office. This type of research is descriptive. The research instrument used was a Likert scale questionnaire with data collection techniques used, namely observation, questionnaires and literature study. The population used in this study were all employees at the Bima City Tourism Office, as many as 61 employees consisting of 37 civil servants (ASN), employees. The sample in this study were all employees at the Bima City Tourism Office, as many as 61 employees, with the sampling technique used, namely the saturated sampling technique, where all members of the population were sampled in the study. The results showed that morale at the Bima City Tourism Office was less than or equal to 70% of the expected (high) acceptable.